The discursive construction of corporate identity in the corporate social responsibility reports: A case study of Starbucks - Li, Xuyan (Frontiers in Psychology, 2022)
Both corporate identity and corporate social responsibilities are of strategic importance to companies’ reputation and competitiveness. From a social constructivist view, identity is constructed in discourse. Therefore, this study sets out to investigate how corporate identity is discursively constructed in corporate CSR communication. Taking Starbucks as an example, this corpus-assisted study explores how Starbucks deploy nomination, predication, and intensification strategies and the corresponding linguistic resources to discursively constructs itself and its main stakeholder groups in the CSR reports from the perspective of Discourse-Historical Approach to Critical Discourse Analysis. The findings show that Starbucks constructs itself as the supportive care-taker of the partners, faithful deliverer of good customer experience, powerful helper of poor farmers, and CSR-conscious selector of suppliers, who takes an strongly-committed and proactive CSR stance. However, behind such discursive construction are the hidden ideologies and corporate agenda of a capitalistic nature, with Starbucks veiling the power dominance and unequal power relations. This study not only contributes to the understanding of the discursive construction of corporate identity, but also helps raise peoples’ awareness of the power game at play behind the corporate discourse.